Punctal occlusion for dry eye syndrome - Ervin, Ann‐Margret (Cochrane Database Syst Rev, 2017)
BACKGROUND: Dry eye syndrome is a disorder of the tear film that is associated with symptoms of ocular discomfort. Punctal occlusion is a mechanical treatment that blocks the tear drainage system in order to aid in the preservation of natural tears on the ocular surface. OBJECTIVES: To assess the effects of punctal plugs versus no punctal plugs, different types of punctal plugs, and other interventions for managing dry eye. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (which contains the Cochrane Eyes and Vision Trials Register) (2016, Issue 11), MEDLINE Ovid (1946 to 8 December 2016), Embase.com (1947 to 8 December 2016), PubMed (1948 to 8 December 2016), LILACS (Latin American and Caribbean Health Sciences Literature Database) (1982 to 8 December 2016), the metaRegister of Controlled Trials (mRCT) (www.controlled‐trials.com; last searched 18 November 2012 ‐ this resource is now archived), ClinicalTrials.gov (www.clinicaltrials.gov; searched 8 December 2016), and the WHO International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en; searched 8 December 2016). We did not use any date or language restrictions in the electronic searches for trials. We also searched the Science Citation Index‐Expanded database and reference lists of included studies. The evidence was last updated on 8 December 2016 SELECTION CRITERIA: We included randomized and quasi‐randomized controlled trials of collagen or silicone punctal plugs in symptomatic participants diagnosed with aqueous tear deficiency or dry eye syndrome. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and extracted data. We contacted study investigators for additional information when needed. MAIN RESULTS: We included 18 trials (711 participants, 1249 eyes) from Austria, Canada, China, Greece, Japan, Mexico, Netherlands, Turkey, the UK, and the USA in this review. We also identified one ongoing trial. Overall we judged these trials to be at unclear risk of bias because they were poorly reported. We assessed the evidence for eight comparisons. Five trials compared punctal plugs with no punctal plugs (control). Three of these trials employed a sham treatment and two trials observed the control group. Two trials did not report outcome data relevant to this review. There was very low‐certainty evidence on symptomatic improvement. The three trials that reported this outcome used different scales to measure symptoms. In all three trials, there was little or no improvement in symptom scores with punctal plugs compared with no punctal plugs. Low‐certainty evidence from one trial suggested less ocular surface staining in the punctal plug group compared with the no punctal plug group however this difference was small and possibly clinically unimportant (mean difference (MD) in fluorescein staining score ‐1.50 points, 95% CI ‐1.88 to ‐1.12; eyes = 61). Similarly there was a small difference in tear film stability with people in the punctal plug group having more stability (MD 1.93 seconds more, 95% CI 0.67 to 3.20; eyes = 28, low‐certainty evidence). The number of artificial tear applications was lower in the punctal plug group compared with the no punctal plugs group in one trial (MD ‐2.70 applications, 95% CI ‐3.11 to ‐2.29; eyes = 61, low‐certainty evidence). One trial with low‐certainty evidence reported little or no difference between the groups in Schirmer scores, but did not report any quantitative data on aqueous tear production. Very low‐certainty evidence on adverse events suggested that events occurred reasonably frequently in the punctal plug group and included epiphora, itching, tenderness and swelling of lids with mucous discharge, and plug displacement. One trial compared punctal plugs with cyclosporine (20 eyes) and one trial compared punctal plugs with oral pilocarpine (55 eyes). The evidence was judged to be very low‐certainty due to a combination of risk of bias and imprecision. Five trials compared punctal plugs with artificial tears. In one of the trials punctal plugs was combined with artificial tears and compared with artificial tears alone. There was very low‐certainty evidence on symptomatic improvement. Low‐certainty evidence of little or no improvement in ocular surface staining comparing punctal plugs with artificial tears (MD right eye 0.10 points higher, 0.56 lower to 0.76 higher, MD left eye 0.60 points higher, 0.10 to 1.10 higher) and low‐certainty evidence of little or no difference in aqueous tear production (MD 0.00 mm/5 min, 0.33 lower to 0.33 higher) Three trials compared punctal plugs in the upper versus the lower puncta, and none of them reported the review outcomes at long‐term follow‐up. One trial with very low‐certainty evidence reported no observed complications, but it was unclear which complications were collected. One trial compared acrylic punctal plugs with silicone punctal plugs and the trial reported outcomes at approximately 11 weeks of follow‐up (36 eyes). The evidence was judged to be very low‐certainty due to a combination of risk of bias and imprecision. One trial compared intracanalicular punctal plugs with silicone punctal plugs at three months follow‐up (57 eyes). The evidence was judged to be very low‐certainty due to a combination of risk of bias and imprecision. Finally, two trials with very low‐certainty evidence compared collagen punctal plugs versus silicone punctal plugs (98 eyes). The evidence was judged to be very low‐certainty due to a combination of risk of bias and imprecision. AUTHORS' CONCLUSIONS: Although the investigators of the individual trials concluded that punctal plugs are an effective means for treating dry eye signs and symptoms, the evidence in this systematic review suggests that improvements in symptoms and commonly tested dry eye signs are inconclusive. Despite the inclusion of 11 additional trials, the findings of this updated review are consistent with the previous review published in 2010. The type of punctal plug investigated, the type and severity of dry eye being treated, and heterogeneity in trial methodology confounds our ability to make decisive statements regarding the effectiveness of punctal plug use. Although punctal plugs are believed to be relatively safe, their use is commonly associated with epiphora and, less commonly, with inflammatory conditions such as dacryocystitis.